Metal Ion Complexes of Kaempferitrin as DNA Topoisomerase I Inhibitors and Its' Cytotoxicities - Ouyang, Xi-Lin; Zhu, Zhi-Ren; Pan, Ying-Ming; Wang, Heng-Shan (Asian Journal of Chemistry, 2015)
In this study, four binuclear M(II) (M = Cu, Zn, Co and Cd) complexes of kaempferitrin were synthesized. Their structures were characterized by elemental analysis, infrared spectroscopy, TG-DTG analysis and MS spectra. The activities of kaempferitrin and its metal complexes on DNA topoisomerase I (TOPO I) were measured by agarose gel electrophoresis using plasmids pBR322 and pUC19 as model substrate DNA. The cytotoxicities of these compounds on MCF-7, SGC-7901, SK-OV-3 and HePG-2 cell lines were determined by MTT assay. The results showed that four complexes could significantly affect the performance of DNA TOPO I to promote its mediated DNA helicase or breakage. Copper complex was identified as an excellent TOPO I Inhibitor. Furthermore, copper complex can inhibit the proliferation of SGC-7901 and SK-OV-3 with the inhibition rate of 44.19 and 44.58 %, stronger than that of the kaempferitrin and other complexes. This study has proved that the kaempferitrin complexes have stronger inhibitory effects than kaempferitrin for potential synergistic effects.